Perancangan Mesin Pengupas Sabut Kelapa - Zahwa Azzahra, Gita; Okta Putra, Ilham; Yuliarman, Yuliarman; Zulhendri, Zulhendri; Yetri, Yuli (Manutech : Jurnal Teknologi Manufaktur, 2023)
Coconut is a major crop in Indonesia. The coconut peeling process consists of several stages, namely the stripping of coir and coconut shells. These processes use manual tools, so it takes a long time and requires manpower. To overcome this problem, the authors design and analyze a coconut husk peeling machine in which the separation process does not mix with peeled coconut husk and is a safe machine to use. while working. This machine uses an automatic system so it does not require extra human labor. The Coconut Coir Peeler Machine is driven by an electric motor. An electric motor that rotates the blade shaft by transmitting power to the shaft through pulleys and belts so that the paring blade rotates. The engine capacity is 1.5 HP, the rotation speed is 1,400 rpm. The transmission system pulley is a drive pulley with a diameter (d1) = 4 inches and a driven pulley (d2) = 8 inches with a Type A Belt. The paring knife used is a flat triangular knife that is circularly arranged like a thread with 50 pieces. on the blade pipe, where the diameter of the blade pipe is 100 mm and the blade height is 40mm.